Analysis Of Factors Influencing Sustainable Palm Oil Plantation Partnership Patterns In Maro Sebo Ilir District, Batang Hari Regency - Nainggolan, Saidin; Hotdame Manalu, Joni (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
This study aims to describe the general characteristics of partnership-based oil palm plantations in Maro Sebo Ilir District, Batang Hari Regency, and to analyze the influence of economic and social factors on sustainable oil palm plantations, including the influence mediated by the institutional performance variable. The economic factors examined include farmers' income, access to capital, and production cost efficiency, while social factors encompass farmers' knowledge levels, participation in farmer groups, and trust and social relationships. Data analysis employed the Partial Least Squares (PLS) method with a sample of 43 farmers. The results indicate that the partnership-based oil palm plantations have been in operation since the transmigration program of the late 1990s, with an average land area of 2.42 hectares and an average partnership duration of 26.3 years; consequently, they are now entering a gradual replanting phase. The economic and social conditions of the plasma farmers fall into the "good" category. Economic and social factors have a positive and significant influence on institutional performance and sustainable oil palm plantations. Social factors exert a significant indirect influence on sustainable oil palm plantations through the institutional performance moderating variable. An R-Square value of 0.705 and a Q-Square value of 0.846 indicate that the model possesses good explanatory power and relevance. KeywordsEconomic Factors, Social Factors, Sustainable, PLS